Critical Examination of Emerging Issues in Refugee Protection: A Transnational Legal Perspective - Gasiokwu, Peter I.; Jenigho P. Esavwede; Aloamaka, Patrick Chukwunonso; Iheanacho, Linda (Magister of Law, Faculty of Law, University of Mataram, 2024)
This research critically examines contemporary challenges in protecting the rights of refugees, focusing on climate-induced displacement and the impact of technology on migration patterns. It identifies significant gaps in current legal frameworks, particularly in their ability to address the transboundary nature of modern displacement. The research highlights the limitations of existing conventions and the need for a more adaptable, transnational legal approach. Key recommendations include expanding the definition of persecution, integrating technology safeguards, and fostering global responsibility-sharing mechanisms. These proposals aim to enhance refugee protection and ensure that legal frameworks remain responsive to the evolving challenges of the 21st century.